Company Valuation and Influencing Factors: A Study of Automotive and Component Manufacturers Listed on the Indonesia Stock Exchange - I Gusti Ngurah Bagus Gunadi; I Gede Cahyadi Putra; Ida Ayu Ratih Manuari (AIBPM Publisher, 2024)
The company's value is crucial as it reflects the company's performance, which can influence investors' perception of the company. The aim of this research is to determine the influence of profitability, company size, liquidity, and managerial ownership on company value in the automotive and component manufacturing sub-sector on the Indonesian Stock Exchange (IDX) for the years 2017-2021. The population in this study consists of manufacturing companies listed on IDX from 2017 to 2021, totaling 13 companies, with a sample size of 12 companies selected through purposive sampling method. This study employed multiple linear regression analysis to investigate the factors influencing company value. The results reveal that profitability and managerial ownership have a positive and significant impact on company value, while company size has no significant effect. Interestingly, liquidity exhibits a negative and significant relationship with company value. These findings suggest potentially important areas for future research. Expanding the study to include additional variables, such as leverage, capital structure, and dividend policies, could provide a more comprehensive understanding of the determinants of company value.